2004
DOI: 10.1089/end.2004.18.743
|View full text |Cite
|
Sign up to set email alerts
|

No Panacea for Drainage after Percutaneous Nephrolithotomy

Abstract: This study did not demonstrate an overwhelming advantage of any one drainage system over the others. All three systems were equally tolerated by patients. There may be less chance of prolonged nephrostomy-site leakage with an 8F pigtail catheter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…However, the tube itself may be associated with increased morbidity [5,6]. Recent randomized studies have shown that, avoiding external nephrostomy tube drainage, termed as the 'tubeless PNL' procedure, significantly decreased pain and morbidity of PNL, and diminished related expenses in selected patients [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the tube itself may be associated with increased morbidity [5,6]. Recent randomized studies have shown that, avoiding external nephrostomy tube drainage, termed as the 'tubeless PNL' procedure, significantly decreased pain and morbidity of PNL, and diminished related expenses in selected patients [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Of 24 studies in this review, 20 made comparisons between the overall duration of procedure [2,3,4,5,6,7,8,9,12,13,14,18,19,20,22,23,24,25,26,27]. In 13 studies [2,4,7,8,9,14,18,19,22,24,25,26,27] the procedure was shorter when tubeless.…”
Section: Resultsmentioning
confidence: 99%
“…In 13 studies [2,4,7,8,9,14,18,19,22,24,25,26,27] the procedure was shorter when tubeless. This was statistically significant for only 1 study [4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the literature shows that a smaller-calibre tube (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) Fr) has been associated with less pain and less urinary leakage compared to larger tubes. [51][52][53][54][55][56] Importantly, there is no further advantage in pain levels to opting for a tubeless approach (i.e., internal ureteral stent) compared to a small-calibre external tube. A 2012 meta-analysis of studies comparing tubes of differing sizes and tubeless approaches concluded that the clinical efficacy and safety of tubeless and small-tube procedures are similar.…”
Section: Laparoscopy and Minimally Invasive Surgery 2014mentioning
confidence: 99%